In Vitro Influence of Prophylaxis Cleaning on Enamel Remineralization with Casein Phosphopeptide-Amorphous Calcium Phosphate - Mona Zeitouny; Hasan Fayyad-Kazan; Herve Tassery; Hussein Fayyad-Kazan (Stilus Optimus, 2020)
Objectives: This randomized controlled in vitro 4-arm trial study aimed to study the remineralization potential of Recaldent™ and assess the effects of prophylaxis cleaning and MI Varnish® on enhancing this remineralization potential. Material and Methods: Sixty human teeth were randomly assigned into equal samples (A/B). Sample A was prophylactically cleaned, randomly divided into equal samples (1/2). Sample A1 received treatment with MI Varnish® and Recaldent™ for 30 days. Sample A2 was treated similarly but without MI Varnish®. Sample B did not receive prophylaxis cleaning and was divided into equal samples (1/2). Sample B1 was treated as A1 and sample B2 as A2. The teeth were examined for mineral composition at baseline, after the interventions (T1), and after prophylaxis cleaning (T2). Study outcomes were mineral content (% weight of carbon [C], phosphorus [P], calcium [Ca], oxygen [O], chlorine [Cl], sodium [Na] and silicon [Si]) and calcium-phosphorus ratio (Ca/P). Results: All groups had similar mineral composition at baseline. At T1, sample B2 exhibited least P, Ca and Ca/P content. Samples A1 and B1 showed higher content of P and Ca, compared to B2 (A1 only exhibited higher Ca/P). Sample A2 exhibited lowest Cl and Na content. At T2, sample A1 exhibited lowest C, P, O and Si content (highest Ca/P). Sample A2 showed least Ca/P, and highest Na content. Conclusions: Teeth treated by Recaldent™ proceeded by prophylaxis cleaning or MI Varnish® showed remineralization, especially when receiving both interventions. This superior effect persisted even after a second cleaning. Further trials are necessary to provide conclusive evidence in humans.